PHARMACOKINETIC CONSIDERATIONS IN SPECIAL PATIENT POPULATIONS: PEDIATRICS, PREGNANCY, AND THE ELDERLY - Abdulrhman Mansour Rizq; Bassam Ali Alahmadi; Fahad Mohammed Alghamdi; Hasan Ayed Alqarni; Nader Mohammed Almalki; Motaz Samir Mandoura (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Pharmacokinetics, the study of how drugs are absorbed, distributed, metabolized, and excreted by the, plays a crucial role in determining the efficacy and safety of medications in patients. Special patient populations, such as pediatrics, pregnancy, and the elderly, present unique challenges in the pharmacokinetic considerations of drug therapy. This essay explores the specific pharmacokinetic considerations in these populations and discusses the implications for clinical practice.